Algorithms and JavaScript Programs in Calculation of R-Functions and Producing Their Two- and Three-Dimensional Charts - Uvarov, Roman A. (NTU "KhPI", 2016)
Usage of HTML5 canvas element suitable for two- and three-dimensional charts of the function is unveiled. Appliance of JavaScript dynamics to this element is implemented. R-functions and level curves construction details are specified. Two- and three-dimension function charts are represented.
Keywords: HTML5; canvas; JavaScript; level curves; theory of R-functions